High value cost conscious care for diabetic patients at a community hospital. Issue 1 (21st May 2015) - Karu, Eric; Shahnazarian, Vahe; Mehta, Parag
Abstract: At New York Methodist Hospital (Brooklyn, NY), the pattern of ordering glucose testing was studied by a multidisciplinary committee because the medicine residents were placing inpatient chemstrip orders at their own discretion. It was found that chemstrip orders were being placed at inappropriate frequencies, and occasionally on inappropriate patients. The staff and residents were educated on daily rounds in order to achieve the goal of reducing unwarranted fingersticks, consequently increasing patient satisfaction and reducing wasted time, resources, and costs. From April 2014 through March 2015 there were 274, 889 fingersticks in the inpatient setting and following the intervention the number of fingersticks had decreased to 238, 187, representing a significant decrease.